Pembatalan Sertifikat Hak Milik Atas Tanah Akibat Cacat Administrasi - Ni Made Silvia Gayatri; I Putu Gede Seputra; Luh Putu Suryani (Jurnal Analogi Hukum, 2021)
Land registration is held to guarantee legal certainty, the completion of land registration is the issuance of a Certificate. The strongest proof of Land Rights is the Certificate, but currently there are many certificates that are not in accordance with the procedure resulting in the issuance of certificates with legal defects or administrative defects, therefore, the authors conducted a study entitled Cancellation of Land Ownership Certificate Due to Administrative Disabilities. By using the formulations of the problem: 1) how is the basis for cancellation of certificate of land rights that are administratively flawed; 2) What are the legal consequences certificates of ownership rights on land with administrative defects. The research method used is a normative research method. In Minister of Agrarian Regulation No. 3 of 1999, article 1 point 12 explains that the basis for cancellation of a certificate can be canceled because the decree contains an administrative legal flaw. Defects Administrative law can be interpreted by a policy or procedure that is not in accordance with applicable law. If there is an administrative defect in the issuance of the certificate, the certificate can be submitted for cancellation. Cancellation of certificate can be through BPN and TUN. The canceled certificate can be renewed or re-registered.